2013
DOI: 10.1088/0957-4484/24/18/185501
|View full text |Cite
|
Sign up to set email alerts
|

Active sensing and damage detection using piezoelectric zinc oxide-based nanocomposites

Abstract: This study investigated the design and performance of piezoelectric nanocomposite-based interdigitated transducers (IDTs) for active sensing and damage detection. First, thin films that are highly piezoelectric and mechanically flexible were designed by embedding zinc oxide (ZnO) nanoparticles in a poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) piezo-polymer matrix. Second, the suspended nanoparticle solutions were then spin coated onto patterned comb electrodes to fabricate the IDTs. The films were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The possibility to use poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE))/ZnO 3 transducers for active sensing and damage detection has also been demonstrated [13]. VDF (co)polymers require relatively high electrical fields of more than 500 kV/cm for complete poling.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to use poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE))/ZnO 3 transducers for active sensing and damage detection has also been demonstrated [13]. VDF (co)polymers require relatively high electrical fields of more than 500 kV/cm for complete poling.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO enhances the piezoelectricity in piezoelectric polymers (Dodds et al 2011). Realizing this, Meyers et al (Meyers et al 2013) have further demonstrated the use of ZnObased nanocomposites as transducer for Lamb wave-based SHM in pipe structure. Thus, ZnO-based nanocomposites hold promising future in development of cost-effective SHM systems for aircraft structures.…”
Section: Piezoelectric Polymer Matrix Nanocompositesmentioning
confidence: 93%
“…Nanocomposites also possess structural and electrical properties that can be tailored by controlling its composition to make them suitable for transducer applications. Piezoelectric PMNC consists of piezoelectric nanofillers like PZT, zinc oxide (ZnO) embedded in a polymer matrix (Daben 1990;Jain et al 2014;van den Ende et al 2007;Meyers et al 2013). These nanofillers impart piezoelectricity simultaneously retaining the properties of the polymer.…”
Section: Piezoelectric Polymer Matrix Nanocompositesmentioning
confidence: 99%
“…Also, randomly oriented electrospun nanofiber mats can be directly used to make a piezoelectric power generator without any extra poling treatment [27]. Nevertheless, fabricated nanofibrous devices still has low output efficiency; many studies to improve the performance of the PVDF nanofibers have been conducted in most of which, the use of nanoparticles such as CNTs, Graghen, BaTiO 3 , and ZnO has led to this improvement [34][35][36][37][38][39][40]. Because of piezoelectric properties, ZnO is one of the viable alternatives to improving performance of nanogenerators [41,42].…”
Section: Introductionmentioning
confidence: 99%